Structural dynamics and vibration in practice : an engineering handbook - Thorby, Douglas (Elsevier/Butterworth-Heinemann, 2008)
This straightforward text, primer and reference introduces the theoretical, testing and control aspects of structural dynamics and vibration, as practised in industry today. Written by an expert engineer of over 40 years experience, the book comprehensively opens up the dynamic behavior of structures and provides engineers and students with a comprehensive practice based understanding of the key aspects of this key engineering topic. Key features Worked example based makes it a thoroughly practical resource Aimed at those studying to enter, and already working in industry; Presents an applied practice and testing based approach while remaining grounded in the theory of the topic Makes the topic as easy to read as possible, omitting no steps in the development of the subject; Includes the use of computer based modelling techniques and finite elements Covers theory, modelling testing and control in practice Written with the needs of engineers of a wide range of backgrounds in mind, this book will be a key resource for those studying structural dynamics and vibration at undergraduate level for the first time in aeronautical, mechanical, civil and automotive engineering. It will be ideal for laboratory classes and as a primer for readers returning to the subject, or coming to it fresh at graduate level. It is a guide for students to keep and for practicing engineers to refer to: its worked example approach ensures that engineers will turn to Thorby for advice in many engineering situations. 1. Presents students and practitioners in all branches of engineering with a unique structural dynamics resource and primer, covering practical approaches to vibration engineering while remaining grounded in the theory of the topic 2. Written by a leading industry expert, with a worked example lead approach for clarity and ease of understanding 3. Makes the topic as easy to read as possible, omitting no steps in the development of the subject; covers computer based techniques and finite elements.